Effect of Enzyme Concentration and Temperature on Viscosity and Betacyanin Content From Pitaya Waste Extract - Mohana, Muniapan (2013)
As synthetic dye has shown up few hazards in contributing in food and textile industries, natural dye has gain its priority in those fields especially in textile sector. In this experiment, pitaya’s waste was selected as a source for natural dye. Thus, there is one obstacle that prevents the natural dye to fulfill the requirements needed in textile industries as the physical properties of the natural dye which is high in viscosity causing it not fasting on cloth which is believed, due to pectin content. In order to come over this problem, this research aim to reduce the viscosity of the natural dye using commercialize pectinase, in a small scale and study the effect of the enzyme concentration and temperature on the reduction of viscosity of the natural dye and also observe the difference in betacyanin content. This experiment was carried out by chemical and also by biological mechanism. Chemical mechanism refers to solvent extraction using water to extract the dye from the fruit, whereas, biological manner refers to usage of enzyme to reduce the viscosity of the natural dye. When enzyme concentration varies form 0.1 % to 5%, the viscosity reduced gradually until the enzyme concentration is 2.5% then the reduction is insignificant. Whereas, the temperature shown a similar result. The highest reduction in viscosity is when the reaction temperature is set at 50oC. It is because, when temperature increases, the rate of reaction will increase and at one point, the rate of reaction will decrease. It is because the enzymes will be denatured at high temperatures. From this research, it is recommended that further studies can be done to the pH and concentration of natural dye in order to obtain low viscosity and high betacyanin content.